Insulin resistance in obese children and adolescents - Monica Cristina dos Santos Romualdo; Fernando José de Nóbrega; Maria Arlete Meil Schimith Escrivão (Elsevier, 2014)
Objective: To evaluate the presence of insulin resistance and its association with other metabolic abnormalities in obese children and adolescents. Methods: Retrospective study of 220 children and adolescents aged 5-14 years. Anthropometric measurements were performed (weight, height, and waist circumference) and clinical (gender, age, pubertal stage, and degree of obesity) and biochemical (glucose, insulin, total cholesterol, and fractions, triglycerides) data were analyzed. Insulin resistance was identified by the homeostasis model assessment for insulin resistance (HOMA-IR) index. The analysis of the differences between the variables of interest and the HOMA-IR quartiles was performed by ANOVA or Kruskal-Wallis tests. Results: Insulin resistance was diagnosed in 33.20% of the sample. It was associated with low levels of high-density lipoprotein cholesterol (HDL-C; p = 0.044), waist circumference measurement (p = 0.030), and the set of clinical and metabolic (p = 0.000) alterations. Insulin-resistant individuals had higher mean age (p = 0.000), body mass index (BMI; p = 0.000), abdominal circumference (p = 0.000), median triglycerides (p = 0.001), total cholesterol (p ≤ 0.042), and low-density lipoprotein cholesterol (LDL-C; p ≤ 0.027); and lower HDL-C levels (p = 0.005). There was an increase in mean BMI (p = 0.000), abdominal circumference (p = 0.000), and median triglycerides (p = 0.002) as the values of HOMA -IR increased, with the exception of HDL-C, which decreased (p = 0.001). Those with the highest number of simultaneous alterations were between the second and third quartiles of the HOMA-IR index (p = 0.000). Conclusion: The results confirmed that insulin resistance is present in many obese children and adolescents, and that this condition is associated with alterations that represent an increased risk for developing metabolic disorders in adulthood. Resumo: Objetivo: Avaliar a presença de resistência à insulina e sua relação com outras alterações metabólicas, em crianças e adolescentes obesos. Métodos: Estudo retrospectivo de 220 crianças e adolescentes de 5 a 14 anos. Foram realizadas avaliações antropométricas (peso, estatura e circunferência abdominal), clínicas (sexo, idade, estágio puberal e grau de obesidade) e bioquímicas (glicemia, insulina, colesterol total e frações, triglicerídeos). A resistência à insulina foi identificada pelo índice HOMA-IR. A análise das diferenças entre as variáveis de interesse e os quartis do HOMA-IR foi realizada pelos testes ANOVA ou Kruskal-Wallis. Resultados: A resistência à insulina foi diagnosticada em 33,20% da amostra. Associou-se a níveis baixos de HDL-C (p = 0,044), medida da circunferência abdominal aumentada (p = 0,030) e ao conjunto de alterações clínicas e metabólicas (p = 0,000). Os indivíduos resistentes apresentaram maiores médias de idade (p = 0,000), IMC (p = 0,000), medida da circunferência abdominal (p = 0,000) e maiores medianas de triglicerídeos (p = 0,001), colesterol total (p ≤ 0,042), LDL-C (p ≤ 0,027) e menores de HDL-C (p = 0,005). Houve aumento das médias de IMC (p = 0,000), medida da circunferência abdominal (p = 0,000) e mediana de triglicerídeos (p = 0,002) à medida que os valores do HOMA-IR se elevavam, com exceção dos níveis de HDL-C que diminuíram (p = 0,001). Aqueles que apresentaram o maior conjunto de alterações simultâneas estavam entre o segundo e terceiro quartis do HOMA-IR (p = 0,000). Conclusão: Os resultados confirmaram que a resistência à insulina está presente em muitas crianças e em muitos adolescentes obesos, e que esta condição está associada a alterações que representam aumento do risco para o desenvolvimento de distúrbios metabólicos na maturidade. Keywords: Child, Adolescent, Obesity, Insulin resistance, Risk factors, Metabolic syndrome, Palavras-chave: Criança, Adolescente, Obesidade, Resistência à insulina, Fatores de risco, Síndrome metabólica